Concept of the Innovation District Development: A Case Study of Yothi Medical and Healthcare Innovation District - Pujinda, Panit; Sanit, Peamsook (Journal of Architectural/Planning Research and Studies (JARS), 2022)
The Innovation District is an urban area that draws innovative firms together and connects them with well-developed infrastructure, tools, and mechanisms which conducive to business and enhance the quality of life, as well as encourage innovation knowledge sharing between clusters. This paper aims to present the development concept of the innovation district using a case study of Yothi Medical and Healthcare Innovation District, which focuses on the development of medical technology and health technology. Case studies of the successfully medical and health innovation districts around the world show that creating the identity of the district is the key element for the development in each type of innovation district. There are two key elements to create a distinctive identity of Yothi Medical and Healthcare Innovation District as follows; (1) defining suitable roles of the original district by focusing on the development of the potentially useful features that can further stimulate the innovation development in the future, as well as developing and promoting physical space according to the defined roles. (2) developing physical space within the innovation district such as physical infrastructure including public utilities and facilities to raise a more efficient use of space. Transportation planning should be integrated with land use planning to facilitate the development and rehabilitation of the original district and turn it into the specific innovation district in the future.